Numerical Analysis of Mass Flow Rate Effect for 18650 Lithium-ion Battery Modules Thermal Management with Liquid Cooling System - Rainer Samuel Fourlando; James Julian; Fitri Wahyuni; Riki Hendra Purba; Fathin Muhammad Madhudhu; Elvi Armadani (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2026)
Effective thermal management is critical for the safety and performance of lithium-ion batteries. This study numerically investigates a liquid cooling system with a mini-channel cold plate, focusing on how different coolant ṁ affect the thermal performance of an 18650 cylindrical lithium-ion battery module. Simulations were conducted using three mass flow rate (ṁ) 0.0001, 0.0003, and 0.0005 kg/s to evaluate their impact on maximum temperature (Tmax) and temperature difference (ΔT). Results show that increasing the ṁ significantly lowers the battery's maximum temperature. besides, increasing the ṁ will cause a higher pressure drop. All configurations successfully maintained excellent temperature uniformity, keeping the temperature difference well below the critical 5°C threshold. Therefore, this study confirms the system's effectiveness and highlights the necessity of optimizing (ṁ) based on the trade-off between thermal efficieny and pressure drop for designing reliable battery thermal management systems.